2023
DOI: 10.6027/temanord2023-515
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated paraffins in urban air in Nordic Countries

Abstract: Background 1.1 Selected compounds 1.2 Selected sampling sites 2. Methods 2.1 Sampling 2.2 Chemical Analysis 2.3 Limit of detection 2.4 Uncertainties 3. Results and Discussion 3.1 Chlorinated paraf ins 4. Conclusions 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Over time, the dominant use of DEHP has been replaced by other ortho -phthalates (e.g., DiNP, DiDP) and alternative plasticizers (e.g., DEHT, DINCH, DEHA, and Octicizer), as demonstrated by the changing substances reported in this study and previous studies on PVC flooring (see Table S24 in the Supporting Information 1). Meanwhile, some regional differences in this industrial transition, especially in alternative plasticizer use, can be observed. For example, the major emerging plasticizers identified in Switzerland in this study are DiDP, DiNP, DEHT, and Octicizer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over time, the dominant use of DEHP has been replaced by other ortho -phthalates (e.g., DiNP, DiDP) and alternative plasticizers (e.g., DEHT, DINCH, DEHA, and Octicizer), as demonstrated by the changing substances reported in this study and previous studies on PVC flooring (see Table S24 in the Supporting Information 1). Meanwhile, some regional differences in this industrial transition, especially in alternative plasticizer use, can be observed. For example, the major emerging plasticizers identified in Switzerland in this study are DiDP, DiNP, DEHT, and Octicizer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the major emerging plasticizers identified in Switzerland in this study are DiDP, DiNP, DEHT, and Octicizer. However, a study in Norway that focused on phosphor plasticizers and flame retardants mainly found TBEP [tris(2-butoxyethyl) phosphate, CASRN: 78-51-3] and TPhP (triphenyl phosphate, CASRN: 115-86-6) . A nontargeted study in the United States found DEHA, DEP, DBP, BBP, TXIB (2,2,4-trimethyl-1,3-pentandiol diisobutyrate, CASRN: 6846-50-0), and ATBC (acetyltributyl citrate, CASRN: 77-90-7) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations